Rancang Bangun Alat Sistem Pembuangan Asap Rokok Pada Smoking Room Menggunakan Sensor MQ 2 Berbasis IoT - Affan Bachri; Moh Ezra Syirojudin (Nucleus Journal, 2022)
Indonesia faces a serious threat, the prevalence of male smokers in Indonesia is the highest in the world, it is estimated that more than 97 million Indonesians are exposed to cigarette smoke. Many ways have been done to reduce the negative impact of cigarette smoke. One of them is the provision of a smoking room. In this study, a tool is made which is a prototype of a special smoking room. This room uses a fan in the form of exhaust in and exhaust out. The design made as a simulation of the room is a box made of 2 mm acrylic which has a size of 23x18x18 cm, in the box there are 2 12 V fans, there is an MQ2 sensor at the top to detect cigarette smoke, then at the bottom left is the ionizer and the top is 1 Watt LED lamp in warm white color. Then for the control box using 2 mm acrylic with a size of 11.5x9x9 cm, at the top there is a 16x2 LCD which is used to display the sensor output results, at the bottom of the LCD there is a power button then an indicator light and a toogle switch which is used to turn on the 1 watt LED light in the simulation box.. Introduction